Interventions to promote physical activity in young people conducted in the hours immediately after school: a systematic review. - Atkin, A; Gorely, T; Biddle, S; Cavill, N; Foster, C (2011)
BACKGROUND: After school is a critical period in the physical activity and sedentary behaviour patterns of young people. Interventions to promote physical activity during these hours should be informed by existing evidence. PURPOSE: The present study provides a systematic review of interventions to promote physical activity in young people conducted in the hours immediately after school. METHODS: The review was conducted in accordance with guidelines from the National Institute for Health and Clinical Excellence. Studies were located through searches of electronic databases, including MEDLINE, EMBASE, PsychINFO and ERIC. For included studies, data were extracted and methodological quality assessed using standardised forms. RESULTS: Ten papers, reporting nine studies, met inclusion criteria. Three studies reported positive changes in physical activity and six indicated no change. Evidence suggests that single-behaviour interventions may be most effective during these hours. CONCLUSION: Limitations in study design, lack of statistical power and problems with implementation have likely hindered the effectiveness of interventions in the after-school setting to date. Further work is required to develop interventions during this critical period of the day.